Assessment of Primary Health Care Attributes in Campina Grande, Paraíba, Brazil - Rafaela Simão de Abrantes; Débora Lana Alves Monteiro; Aline de Paula Rêgo Graciano Luz; Ricardo Alves de Olinda; Wilton Wilney Nascimento Padilha (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to assess the presence and extent of Primary Health Care attributes in Campina Grande, Paraíba. Method: this is a cross-sectional study with 202 professionals from the Basic Health Units. The Primary Care Assessment Tool, Brazil, was used, which includes eight attributes of primary care whose scores were converted into a scale from 0 to 10, with those considered satisfactory > 6.60. Result: the general score mean was 7.6, but First contact access obtained a score of 3.7. Dental surgeons attributed the worst scores for all attributes (p <0.05). Permanent education activity was associated with a high general score (p <0.01). Conclusion: with the exception of First contact access, the other attributes are present, but initiatives by teams and managers are necessary for its expansion, with permanent education being the main strategy in this process.